2006
DOI: 10.1038/sj.onc.1209893
|View full text |Cite
|
Sign up to set email alerts
|

Parafibromin is a nuclear protein with a functional monopartite nuclear localization signal

Abstract: Parafibromin is a nuclear protein with a tumour suppressor role in the development of non-hereditary and hereditary parathyroid carcinomas, and the hyperparathyroidism-jaw tumour (HPT-JT) syndrome, which is associated with renal and uterine tumours. Nuclear localization signal(s), (NLS(s)), of the 61 kDa parafibromin remain to be defined. Utilization of computer-prediction programmes, identified five NLSs (three bipartite (BP) and two monopartite (MP)). To investigate their functionality, wild-type (WT) and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 28 publications
2
50
1
Order By: Relevance
“…Binding of β-catenin/parafibromin may be mediated by protein tyrosine phosphatase, PTPN11 (Shp2), which dephosphoylates parafibromin and thus allows it to bind β-catenin, recruit the PAF complex, and activate transcription (13). Interestingly, loss-of-function mutations within the coding sequence of parafibromin lead to parathyroid adenomas and ossifying fibromas of the jaw (412)(413)(414). Further work using cell-specific knock-outs are needed to help determine how these regulators of β-catenin/TCF-mediated transcription govern bone formation.…”
Section: Other Components Of the Nuclear β-Catenin Transcriptional Comentioning
confidence: 99%
“…Binding of β-catenin/parafibromin may be mediated by protein tyrosine phosphatase, PTPN11 (Shp2), which dephosphoylates parafibromin and thus allows it to bind β-catenin, recruit the PAF complex, and activate transcription (13). Interestingly, loss-of-function mutations within the coding sequence of parafibromin lead to parathyroid adenomas and ossifying fibromas of the jaw (412)(413)(414). Further work using cell-specific knock-outs are needed to help determine how these regulators of β-catenin/TCF-mediated transcription govern bone formation.…”
Section: Other Components Of the Nuclear β-Catenin Transcriptional Comentioning
confidence: 99%
“…A clear functional nuclear localization signal (NLS) was not identified until one study reported that parafibromin contains a functional bipartite (BP) NLS (Hahn and Marsh, 2005). However, a recent report reveals that it contains five putative NLSs, three BP and two monopartites (MP) (Figure 1b), and that only one of these is evolutionarily conserved and functions as MP NLS (Bradley et al, 2007). The behavior of parafibromin reported so far in cancers is its potential function as a tumor suppressor.…”
Section: Pd2/hpaf1 Is a New Candidate Oncogenementioning
confidence: 99%
“…Parafibromin, the 531 amino acid protein encoded by the HRPT2 gene (15), is part of the human Paf1 complex and involved in transcription regulation, histone modification and cell proliferation (16)(17)(18)(19)(20)(21). It has been shown that parafibromin down-regulates the expression of cyclin D1 (16,20).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that parafibromin down-regulates the expression of cyclin D1 (16,20). The protein is mostly located in the nucleus and the nuclear localization signal (NLS) was originally identified at residues 125-139 (19) and most recently at residues 136-139 (21). Inactivating mutations of parafibromin were reported in 77% of sporadic parathyroid carcinomas (11)(12)(13) and loss of immunoreactivity for parafibromin was shown in the majority of parathyroid carcinomas (22,23).…”
Section: Introductionmentioning
confidence: 99%